Penguatan Literasi Ekonomi dan Keuangan Syariah dalam Rangka Kemandirian Ekonomi Masyarakat Petani Pasca Pandemi Covid-19 - Rudy Haryanto; Fadlan; Didin Burhanuddin Rabbani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The Covid-19 pandemic has introduced a lesson in itself for the humans of Prancak Village, Pasongsongan District, Sumenep Regency. This occasion gave the impact of a turning factor in existence to attract towards the Creator, now no longer most effective for topics of hablumminallah however additionally hablumminannas, specifically withinside the monetary sector. The farming network in fashionable is aware about the significance of sharia monetary transactions, they experience this whilst monetary get entry to is tough or confined for the duration of a pandemic. Their hobby withinside the Islamic monetary device which objectives to get benefits from Allah SWT started to emerge. They consider this, specifically the various farming network if you want to deepen understanding of Islamic economics and finance. Not most effective for doing commercial enterprise, however in dealing with the every day financial system and budget in order that it's far greater green to create monetary independence. This count number does now no longer prevent there, as a way to foster a spirit of doing commercial enterprise or including fee to its products, specifically agricultural products. So the schooling and counseling application withinside the shape of Community Service (PKM) from FEBI IAIN Madura collaborated with village officers with a view to offer answers associated with sharia monetary and monetary understanding or literacy that the farming network without a doubt wanted. The schooling and counseling strategies introduced are face-to-face strategies, concerning strengthening Islamic monetary and monetary literacy withinside the context of monetary independence of farming groups after the Covid-19 pandemic. The outcomes of the evaluation of the information received display that the schooling members examine that the schooling fabric may be implemented of their commercial enterprise even in dealing with the every day own circle of relatives financial system, they experience satisfied and influenced and experience greater assured to create sharia-primarily based totally monetary independence as a way to wish for the blessing and benefits of Allah SWT.